Hadith and the Tradition of Islamic Boarding School Scholars: A Theoretical Study of the Yellow Book, the Talaqqi Method, and the Authority of the Sanad - Ahmad Maddah Hamdani; Ahmad Mohammad Tidjani (Al-Iffah: Journal of Islamic Sciences Research, 2025)
This study explores the position of hadith within the pesantren educational system, focusing particularly on the kitab kuning tradition, the methods of talaqqi and musyāfahah, the role of the kiai as the authoritative bearer of scholarly sanad, the pesantren’s value system rooted in prophetic teachings, and the integration of hadith studies into the modern pesantren framework. Employing a library research approach, the study examines key concepts and findings from a range of relevant scholarly works. The analysis demonstrates that hadith constitutes both the epistemological and spiritual foundation of pesantren education. It functions not only as a source of legal and moral guidance but also shapes the distinctive modes of knowledge transmission and educational ethos within the pesantren tradition. Modern pesantren, in turn, strive to integrate hadith studies into contemporary educational structures while preserving the authenticity of the sanad-based tradition. In this way, hadith serves as the intellectual and spiritual core that sustains the continuity of knowledge, ethical conduct, and Islamic spirituality in the pesantren milieu.